2020
DOI: 10.1089/bfm.2020.0195
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Composition of Expressed Fresh Human Milk

Abstract: Breast milk is considered the ideal and preferred feeding for all infants through the first 4-6 months of life. It provides many short and long-term benefits to the infant and mother. In the absence of breastfeeding, expressed breast milk is the best way to provide nutrition. In the United States, the majority of breastfeeding mothers express milk at some point during the course of lactation. Breast milk is a dynamic fluid and its content changes with duration of lactation and varies between and among women. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 89 publications
(88 reference statements)
1
22
1
1
Order By: Relevance
“…The composition of human milk is dynamic and depends on different factors, including host genetics, environment and gestational age [1]. As a result, own mother's milk (OMM) is widely acknowledged as the best feeding option for preterm infants [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of human milk is dynamic and depends on different factors, including host genetics, environment and gestational age [1]. As a result, own mother's milk (OMM) is widely acknowledged as the best feeding option for preterm infants [2].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin concentrations in DHM before (raw) and after HTST treatment (processing at 70, 72 and 75 • C for 15, and 25 s) or HoP (62.5 • C, 30 min) (n = 5) 1. …”
mentioning
confidence: 99%
“…The most abundant FA in milk are SFA, followed by MUFA and PUFA, and these compounds-expressed as % of FA-are mutually dependent, with an increase in one FA implying a decrease in one or more other FA [35]. Among FA, PUFA tend to be more sensitive to maternal dietary intake [10]. A cross-countries study showed that the proportions of SFA and MUFA were relatively constant across a large number of countries, whereas the level of some PUFA, and particularly DHA, was highly variable, likely due to maternal diet influences [37].…”
Section: Discussionmentioning
confidence: 99%
“…The composition of human milk depends on different environmental and maternal factors [10][11][12][13]. Maternal dietary habits have been reported to influence human milk fatty acids (FA) composition, while macronutrient contents in milk appear less sensitive to maternal dietary intakes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors and the manner in which HM is handled can affect HM's composition [23]. During the storage and processing of expressed HM, there are risks of bacterial contamination, decreased immunological activity, and reduced nutritional potential [24]. The Sri Lankan health agency strongly recommends against the use of pumps to express human milk.…”
Section: Discussionmentioning
confidence: 99%